Dental caries development among African-American children: results from a 4-year longitudinal study - Lim, Sungwoo (Community Dent Oral Epidemiol, 2014)
OBJECTIVE: To examine dental caries development and caries risk factors among preschool African-American children from low-income families in Detroit, Michigan over a four- year window. METHODS: Data came from a representative sample of 1,021 children (zero to five years) and their caregivers in Detroit. The baseline participants in 2002–03 (W1) were reexamined in 2004–05 (W2) and 2007 (W3). Caries was measured using the International Caries Detection and Assessment System. Bivariate and multivariate analyses for repeated data were conducted to explore associations between caries increment outcomes and demographics, access to dental care, oral health-related behaviors, and social and physical environments. RESULTS: The mean number of new NCCL (non-cavitated caries lesions) was 2.8 between W1 and W2 and 2.6 between W2 and W3, while the mean number of new CCL (cavitated caries lesions) was 2.0 and 2.0, respectively, during the same time periods. In younger children (< three years old in W1) higher number of new NCCL than new CCL were observed in both W1–W2 and W2–W3. The risk of new NCCL was associated with child’s soda intake and caregiver’s age. For the risk of new CCL, significant risk factors included baseline NCCL, baseline CCL, as well as child’s age. Baseline caries and child’s soda intake were also associated with the risk of developing new decayed, missing, and filled tooth surfaces. CONCLUSIONS: Higher number of new NCCL relative to CCL was developed among low-income Africa-American children during early childhood. New caries development was associated with baseline caries and child’s soda intake.